Pelatihan Pembuatan Media Pembelajaran Jarak Jauh Pada Masa Pandemi Covid-19 Bagi Para Guru Di SMP Negeri 1 Karang Bahagia Kabupaten Bekasi - Siti Sahara; Sylvira Ananda Azwar (Jurnal TUNAS, 2021)
Large-scale Social Restriction Policy (PSBB) resulted in all activities carried out outside the home must be stopped until the Covid-19 pandemic subsides, not least the karang Bahagia district of Bekasi Regency. This transforms the learning process in class into distance learning. Based on direct observation with partners, namely SMPN 1 Karang Bahagia found that 80% of teachers use the WhatsApp application in the distance learning process. Therefore, the implementation of Community Service takes the theme of making distance learning media in the Covid-19 pandemic. The purposeiof Community Service is to fulfill the activities of Tridharma Higher Education byiproviding counseling to teachers in karang Bahagia district of Bekasi regency and surrounding areas in order to create interesting learning media so as to increase the learning motivation of students. This activity has been carried out via the zoom meeting application with excellent responses from teachers in karang Bahagia district of Bekasi regency and surrounding areas. This can beiseen from the numberiof participants consisting of 143 teachers and the increase in knowledge about the creation of learning mediaibased on the results ofkpre-test andkpost-test participants.